Emotional intelligence, self-efficacy and job performance of university lecturers / Nurhamizah Ishak - Ishak, Nurhamizah (Research Management Centre (RMC), 2021)
This study looks at the relationship between emotional intelligence and self-efficacy towards job performance amongst lecturers of a centre of foundation studies owned by a public university in Selangor. Data was collected through a questionnaire on the sample of 86 lecturers. The findings revealed there were significant and positive relationship between emotional intelligence and self-efficacy towards job performance. All four emotional intelligence dimensions namely: regulation of emotion, self-emotional appraisal, use of emotion and others emotional appraisal; as well as all three self-efficacy dimensions namely: teaching, research and other academic or service-related activities also are positively correlated with job performance. In addition, it was found that both emotional intelligence and self-efficacy contributed to the lecturers' job performance despite its small percentage. As for the implications of this study, it contributes to the corpus of knowledge in the area of emotional intelligence, self-efficacy and job performance among lecturers in Malaysia context.